Outsourced eye care in the Finnish capital region: Switching from fee-for-service to bundled payment model - Moisander, Susanna; Moilanen; Jukka Ari Olavi; Backström; Hans Henrik Konstantin; Marjasova, Olga; Myöhänen, Marko Juhani; Nykänen, Taina Pauliina; Pietilä, Mikko Juhani; Torkki, Paulus (WILEY, 2025)
Purpose The demand for specialised eye care has quadrupled over the last two decades, driven by an aging population and the advent of new treatments. This surge has led to increased outsourcing by the Helsinki and Uusimaa Hospital District (HUS) Eye Hospital, initially relying on a fee-for-service model. This model, however, has been marked by excessive bureaucracy and transaction costs. Between 2019 and 2021, HUS Eye Hospital embarked on a comparative analysis of outsourcing models to identify the most cost-effective, efficient and suitable approach.
Methods After the review of literature and stakeholder interviews, three different outsourcing models were assessed: fee-for-service, capitation and bundled payment. The models were evaluated against each other and HUS insourcing using SWOT analysis, custom-made evaluation matrices and cost analysis.
Results The evaluation identified bundled payments as the most promising model for HUS eye care outsourcing. Under this model, patients diagnosed with or suspected of having eye diseases are referred to external service providers for a predetermined period, encompassing follow-up and treatment, with providers receiving a fixed payment for each assigned patient.
Conclusion Determining the optimal outsourcing model for HUS Eye Hospital was a complex process and necessitated the development of a new quality control system. The selection of bundled payment as the preferred method required an adaptation of it to the national requirements and legislation. While bundled payments have been successfully implemented in other medical specialties, their application in ophthalmology is novel, with forthcoming data from HUS Eye Hospital expected to shed further light on its effectiveness.